Detection of Hammondia heydorni-like oocysts in feces of a dog with recurrent diarrhea - Steffl, Martin; Nautscher, Nadine (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2019)
We report a male, 15-month-old American Canadian White Shepherd dog suffering from recurrent diarrhea and anorexia. Fecal analysis revealed coccidian oocysts of small size. Their morphology was similar to those of Hammondia (H.) heydorni and Neospora (N.) caninum isolates. Unsporulated oocysts had a mean length of 11.8 ± 0.96 µm and a mean width of 11.9 ± 0.96 µm. H. heydorni infection was suggested based on the larger size compared with N. caninum oocysts. Additionally, real time PCR analysis for N. caninum from the fecal sample was negative. After a single anti-coccidian treatment (0.45 mg/kg emodepside + 9 mg/kg toltrazuril) accompanied by amoxicillin (12 mg/kg twice daily for 6 days) the dog recovered very quickly from the disease. This case demonstrates that H. heydorni-like oocysts may be associated with gastrointestinal disease in canine species.
Keywords: Gastro-intestinal disease; young dog; Hammondia heydorni; coccidian oocysts; treatment